Poizvedovanje in individualne razlike - Vilar, Polona (Knjižnica, 2008)
The paper presents individual differences, which are found in studies of information retrieval with emphasis on models of personality traits, cognitive and learning styles. It pays special attention to those models which are most often included in studies of information behaviour, information seeking, perceptions of IR systems, etc., but also brings forward some models which have not yet been included in such studies. Additionally, the relationship between different individual characteristics and individual's chosen profession or academic area discussed. In this context, the paper presents how investigation of individual differences can be useful in the design of IR systems.
Keywords: poizvedovanje; individualne razlike; osebnostne poteze; kognitivni stili; učni stili; sistemi za poizvedovanje; načrtovanje